The Implementation of Good Governance-Based Protocol Management to Enhance the Leadership Image of the Regional Head in Hulu Sungai Utara Regency - Taqiyuddin, Muhammad Shaufi; Kristanto, Budi (Jurnal Ilmiah Ilmu Administrasi Publik, 2025)
This study analyze the implementation of good governance-based protocol management in enhancing the leadership image of the regional head in Hulu Sungai Utara Regency. The research employed a qualitative approach with a case study design. Data were collected through in-depth interviews, observations, and documentation studies involving eleven informants from the Protocol and Leadership Communication Division of the Regional Secretariat of Hulu Sungai Utara Regency. Source and method triangulation techniques were used to ensure data validity, while data analysis followed the interactive model of Miles and Huberman. The results show the principles of good governance have been applied in protocol management through four main aspects: transparency, accountability, effectiveness, and professionalism. Transparency is reflected in the openness of official activity information shared through internal media and online publications. Accountability is demonstrated through the preparation of comprehensive and periodic activity reports. The effectiveness of the protocol team is evident in strong inter-departmental coordination and adaptability to field conditions, while professionalism is reflected in discipline, work ethics, and adherence to protocol standards in appearance and conduct. However, the study also identifies several challenges, including limited human resources, the dense schedule of the regional head’s activities, and the suboptimal use of information technology for digital documentation. Overall, the implementation of good governance-based protocol management has positively contributed to improving the leadership image of the regional head. Well-organized, transparent, and professional official activities have shaped public perceptions of credible, open, and authoritative leadership.